Overlap coefficient for placing round-shaped details processed on the vibration development machine tools determining - Gavrilchenko, O. V.; Zakharov, V. M. (Видавництво Львівської політехніки, 2013)
Описаний принцип обрахування коефіцієнта перекриття для деталей круглої форми. The principle of overlap coefficient calculation for round-shaped details has been.